D-band Millimeter Wave Generation and Transmission Though Radio-Over-Fiber System - Jing Ling Li; Feng Zhao; Jianjun Yu (IEEE Photonics Journal, 2020)
A D-band vector millimeter wave (mm-wave) signal generation and propagation scheme employing cascaded intensity modulator (IM) and in-phase/quadrature (I/Q) modulator is proposed and implemented. In experiment, both the IM and I/Q modulator are operating on optical-carrier-suppressing (OCS) mode to generate two pairs of dual single-sideband (SSB) signals, and the undesired optical sidebands are not eliminated by an optical filter. For each pair of dual SSB signals, one is unmodulated the other is vector-modulated, they are located on both sides of the center suppressed carrier. After optical fiber transmission, SSB signals will beat with each other at the photoelectric detection end, thus the electrical mm-wave signals are generated. We experimentally demonstrated 2-Gbaud 16QAM, 4-Gbaud QPSK, and 8-Gbaud QPSK Radio-over-Fiber (RoF) transmission at 130-GHz over 22.5 km standard single mode fiber and 1 m wireless link with a Bit-Error-Rate (BER) under ${3}{{.8}} × {1}{{0}^{{{ - 3}}}}$ .